Field Electron Emission Performance And Orthodoxy Test Of Tungsten Emitters With And Without Thin Tungsten Trioxide Barrier - Burda, Daniel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
This initial study aims to explore the topic of thin barrier layers for single tip cold field emitters. The experiment and measurements have been conducted in ultra-high vacuum field electron microscope. Additionally, micrographs of the emitter were obtained using scanning electron microscope. The performance of the emitter was evaluated using orthodoxy test and Murphy-Good plots, which can give more complete picture of emitter changes during field emission.
Keywords: Cold field emission; single tip field emitters; tungsten tip; self-heating of electron emitter; tungsten trioxide; dielectric barrier; Murphy-Good plot